Social and Behavioral Determinants for Early Childhood Caries among Preschool Children in India - Mitali Jain; Ritu Namdev; Meenakshi Bodh; Samir Dutta; Parul Singhal; Arun Kumar (Tabriz University of Medical Sciences, 2015)
Background and aims. Early Childhood Caries (ECC) is a public health problem with biological, social and behavioural determinants and the notion that the principal etiology is inappropriate feeding modalities is no longer tenable. Hence this study was undertaken to assess the relationship between ECC and socio-demographic factors, dietary habits, oral hygiene habits and parental characteristics. Materials and methods. The study involved a dental examination of 1400 children aged 0‒71 months, recording caries using Gruebbel's deft index and a structured questionnaire to interview parents or caretakers. The tabulated data was statis-tically analyzed using t-test and ANOVA at 5% level of significance. Results. The variables significantly associated with ECC were age (P<0.001), geographical location (P<0.05), duration of breast/bottle feeding (P<0.001), use of sweetened pacifiers (P<0.001), frequency of snacking (P<0.05), frequency of tooth brushing (P<0.001), the person responsible for child's oral health care (P<0.05) and education level of parents (P<0.05). However, other variables like child's gender, number of siblings, types of snack the child preferred and age at which tooth brushing was instituted did not have statistically significant relationship with ECC (P>0.05). Conclusion. ECC is preventable and manageable with proper information and skills. It is important for healthcare profes-sionals, family physicians and parents to be cognizant of the involved risk factors as their preventive efforts represent the first line of defense.